2020
DOI: 10.21154/cendekia.v18i2.1886
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Character Education Based on Golden Habits at SMP Muhammadiyah 1 Depok Yogyakarta

Abstract: This research is motivated by a deterioration in character values characterized by frequent psychological or moral violence. This type of research is qualitative research with a descriptive approach. This research was conducted in SMP Muhammadiyah 1 Depok Yogyakarta. The data gathered from the principal, assistant principal of curriculum, assistant principals of students› affairs, and five teachers of Ismuba. The results of this study showed: firstly, the planning of the strengthening golden habits character e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…The results showed that the management of religious education learning in conflict-prone zone schools includes three aspects, namely planning, implementation and evaluation. These results support the findings of previous research which states that the implementation of learning in schools includes planning, implementation and evaluation (Firman & Hidayat, 2020). Schools are required to perform a planning process guided by the Minister of National Education No.…”
Section: Religious Education Learning Managementsupporting
confidence: 89%
“…The results showed that the management of religious education learning in conflict-prone zone schools includes three aspects, namely planning, implementation and evaluation. These results support the findings of previous research which states that the implementation of learning in schools includes planning, implementation and evaluation (Firman & Hidayat, 2020). Schools are required to perform a planning process guided by the Minister of National Education No.…”
Section: Religious Education Learning Managementsupporting
confidence: 89%
“…Hasan Langgulung in Firman (2017) states that the word fitrah in Arabic has the meaning of being a creation or made by God, in the sense that man has been given good potential by Allah. Therefore, even if not educated, man will naturally conform to the teachings of religion, because it has been created according to it, unless the person is educated otherwise, that is, educated to deny religion (Firman & Hidayat, 2020). This explains that human nature tends to goodness, truth, beauty, glory and holiness.…”
Section: Discussionmentioning
confidence: 99%
“…In order to create educational goals, the curriculum must be able to improve its quality. The curriculum must be able to adapt to the situation of each good school, paying attention to the needs and stages of development of students as well as the needs of national development while keeping in mind that national education is based on national culture and national education based on Pancasila and the Constitution 1945 [7,8]. To continue to improve the quality of education in Indonesia, the curriculum applied is developing, adjusting to the education unit, regional potential, and it is necessary to evaluate the extent to which the effectiveness of curriculum implementation.…”
Section: Literature Reviewmentioning
confidence: 99%